Assessment of venous thromboembolism awareness among surgical ward patients in Hail, Saudi Arabia: a cross-sectional study - Alrashid, Fauwaz; Idris, Saadeldin Ahmed; Alshammari, Dalal Saad; Alshammari, Maryam Abdullah; Alahmed, Shog Khalid (International Journal of Research in Medical Sciences, 2025)
Background: Venous thromboembolism (VTE), including deep vein thrombosis (DVT) and pulmonary embolism (PE), is a major cause of morbidity and mortality among hospitalized patients in Saudi Arabia. However, there is limited data on VTE awareness in the northern region. This study aimed to assess the awareness and perceptions of VTE and thromboprophylaxis among surgical ward patients in Hail, Saudi Arabia. Methods: A descriptive cross-sectional study was conducted at King Khalid Hospital from September to December 2024, involving 300 patients hospitalized in the surgical ward for more than three days. Patients with shorter hospital stays, cognitive impairments, language barriers, or a previous VTE diagnosis were excluded. Results: Patients with higher education and those who had received pharmacological or non-pharmacological thromboprophylaxis showed significantly greater knowledge of VTE (p<0.05). No significant associations were found between knowledge scores and age, gender, admission reason, or personal/family VTE history (p>0.05). A positive correlation was observed between knowledge and attitude scores (r=0.132, p=0.037). Conclusions: The study revealed low awareness of VTE, its symptoms, and risk factors among surgical patients. It highlights the importance of educational initiatives by healthcare providers to enhance patient understanding and support VTE prevention.